PENINGKATAN MUTU GENETIK INDUK DAN CALON INDUK KAMBING PE PROLIFIK MELALUI PEMANFAATAN PAKAN KULIT BUAH KAKAO - Zulkharnaim -; Jasmal A Syamsu; Muhammad Ihsan A Dagong; Sahiruddin Sabile (Universitas Islam Balitar, 2016)
Pod husks from waste cocoa crops used as alternative feed goats Peranakan Etawah. This study aims to determine the impact of the pod husks as a feed supplement to increase body size of adult female and parent in preparing for pregnancy. A total of 30 goats were divided into 16 tails dara and 14 breeding, reared intensively for 60 days. Pod husks were feeding as many as 1000-1500 g / head / day. The analysis used the PCR RFLP. The results showed the average growth of Body Lenght for the adult female, the prolific parent and single parent respectively by 1.75, 2:18 and 1:59 cm, while the average increase respectively Shoulder Height 1:49, and 1:12 1.97 cm. The results of the analysis of PCR RFLP GH MspI produced three genotypes, namely TT; TC and CC. Obtained genotype frequencies of TT (0091); TC (0409) and CC (0500). GH MspI gene polymorphism is not associated with the prolific nature, but related with the average increase in body size. It can be seen in the TT genotype showed the average increase Body Lenght (2.26 cm) and Shoulder Height (1.80), while TC and CC is almost the same (not different). Program selection on the growth potential of goats can use TT genotype.